1994
DOI: 10.1111/j.1559-1816.1994.tb01549.x
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Resistance to Mergers Between Groups1

Abstract: Workers involved in a business merger often display strong ingroup/outgroup biases that can threaten the merger's success. Social identity theory helps to explain why and when such problems will occur. Using that theory, strong cohesion and successful performance were identified as two characteristics of a workgroup that should increase its resistance to a merger. An experiment involving mergers between small task groups was conducted to test this claim. Each group's cohesion and performance was used to predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
131
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(143 citation statements)
references
References 64 publications
10
131
0
1
Order By: Relevance
“…A similar finding was obtained in a laboratory study by Haunschild et al (1994), who found that more successful groups showed more resistance to a merger and displayed stronger ingroup biases than less successful groups. If members of the dominant or more successful group experience the merger more as a continuation of their pre-merger group identity than members of the nondominant group (as demonstrated by Terry et al, 2001;van Knippenberg et al, 2002), then why would members of the dominant group show more ingroup bias than members of the nondominant group?…”
Section: Continuing Group Identitiessupporting
confidence: 64%
See 2 more Smart Citations
“…A similar finding was obtained in a laboratory study by Haunschild et al (1994), who found that more successful groups showed more resistance to a merger and displayed stronger ingroup biases than less successful groups. If members of the dominant or more successful group experience the merger more as a continuation of their pre-merger group identity than members of the nondominant group (as demonstrated by Terry et al, 2001;van Knippenberg et al, 2002), then why would members of the dominant group show more ingroup bias than members of the nondominant group?…”
Section: Continuing Group Identitiessupporting
confidence: 64%
“…These merging groups often hold a special importance to their members, particularly in their capacity to form a basis for self-definition (Brewer & Miller, 1996;Deaux, 1996;Hogg & Abrams, 1988;Tajfel & Turner, 1986). In previous research on mergers, it has therefore been suggested that negative reactions to a merger may stem from the fact that mergers force group members to forfeit their pre-merger group identity and adopt a new one (e.g., Haunschild, Moreland, & Murrell, 1994). However, no empirical study to date has directly investigated how reactions to a merger are rooted in the pre-merger group identity.…”
Section: Corporatemergersandtheireffectsonthepersonnelmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first discussion, participants rank ordered the usefulness of 10 items available after an airplane crash in Northern Minnesota (a standard task; e.g., Haunschild, Moreland, & Murrell, 1994). In the second discussion, participants rank ordered 10 possible solutions to the parking problem on campus.…”
Section: Methodsmentioning
confidence: 99%
“…For mergers to be successful those leading a company need to implement the merger in ways that successfully engage their employees in the new company created by the merger and in its culture. In other words, mergers present a challenge to leaders who must implement the change in ways that motivates the cooperation of their employees in the new company in a situation in which valued identities are threatened and may need to change (Anastasio, Bachman, Gaertner, & Dovidio, 1997;Haunschild, Moreland, & Murrell, 1994;Hogan, Curby, & Hogan, 1994;Skevington, 1980;Terry & Callan, 1998;Terry, Callan, & Sartori, 1996;Terry, Carey, & Callan, 2001;Terry & O'Brien, 2001).…”
Section: Introductionmentioning
confidence: 99%